Theoretical And Empirical Studies Of The Use Of Problem Base Learning In The Technical And Vocational Education And Training (TVET) In The Context Of The XXI Century (ILIN Institute Makassar, 2019)
The research aims to find out: (1) how far PBL has been used as a learning model in the vocational environment; and (2) how far is the influence of PBL on learning outcomes? The study was conducted with literature studies through theoretical and empirical studies of references and relevant research results, and continued with focus group discussions (FGD). The relevant references include learning theories, and theories about problem base learning (PBL). While the study of the results of relevant research, is a study of studies on the influence of PBL on